منهج سعيد النورسي في التعامل مع الحاديث المتشابهات في رسائل النور = The methodology of Said Nursi in dealing with Hadith Mutashabihat in "Risale al-Nur" = Metodologi Said Nursi dalam menangani hadith mutashabihat di dalam "Risale al-Nur" - Fatah Yasin, Raudlotul Firdaus; Che Rahim, Nur Aina Mardhiyah (IIUM Press, International Islamic University Malaysia, 2020)
يهدف البحث إلى توضيح منهج سعيد النورسي في التعامل مع الأحاديث المتشابهة من خلال كتابه "رسائل النور" ببيان كيفية منهجه في إيراد المعنى المراد بالأحاديث المتشابهة حيث حللت الباحثة الأحاديث المتشابهة فيه عن درجاتها أو مرتبتها، واستخرجت الأحاديث من كتب الأحاديث مع ذكر تخريجها. ثم استعملت الباحثة المراجعة والمطالعة بتناول آراء المحدثين عنها، وذكر النتائج لكل منها، كما أنها تحلل المشكل وتوضح المبهم. ****************************************************************************** The research aims at clarifying the approach of Said al-Nursi in dealing with hadīth mutashābihāt through his book Rasā’il al-Nūr" by analysing his approach in explaining the hidden meaning of the hadīth. This is done by identifying the degree or rank of the hadīth and extracting the narrators as well as the citation and extraction of hadith from its sources. Then the researcher used the review and comparative methodology to take up the views of the hadīṣ scholars (muÍaddithīn), and mentioned the results for each. ********************************************************************************* Penyelidikan ini bertujuan untuk menjelaskan pendekatan Said Nursi dalam menangani hadīth mutashābihāt di dalam karya beliau "Risalah al-Nur". Ini dilakukan dengan menganalisis pendekatan Said Nursi dalam menjelaskan maksud hadith yang tersirat dengan mengenal pasti status hadith, perawi dan sumber hadis. Kemudian penyelidik menggunakan kajian nilaian semula dan metodologi perbandingan untuk mengambil pandangan para naratif muhaddith, dan menyatakan hasil natijah masingmasing.